2009
DOI: 10.1136/adc.2008.157305
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of mothers and infants exposed to antenatal amphetamines

Abstract: Amphetamine-exposed mothers and infants in public hospitals of NSW and the ACT are at significantly higher risk of adverse social and perinatal outcomes even when compared with mothers and infants exposed to other drugs of dependency. Increased vigilance for amphetamine exposure is recommended due to a high prevalence of use, especially in Australia, as a recreational drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 25 publications
4
57
0
2
Order By: Relevance
“…While the findings of this study are similar to other studies, it showed that children of addicted mothers experience severe and sustained trauma and have a range of psychological and psychiatric nosology and problems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The severity of the behaviors as an effect of experiencing trauma should not be underestimated, as these children have experienced trauma for a prolonged period of time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While the findings of this study are similar to other studies, it showed that children of addicted mothers experience severe and sustained trauma and have a range of psychological and psychiatric nosology and problems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The severity of the behaviors as an effect of experiencing trauma should not be underestimated, as these children have experienced trauma for a prolonged period of time.…”
Section: Discussionsupporting
confidence: 89%
“…Children of drug addicted parents experience ongoing and multiple levels and forms of trauma [1,2] and these damaging experiences lead to several psychological problems and psychiatric nosology along with comorbid symptomologies [3][4][5][6][7][8]. Regular and ongoing exposure to trauma is likely to have a significantly negative impact on the development of children (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient, regularly moving from house to house) and unstable lifestyle as a result of being addicted to drugs in general. Amphetamines decrease the gestational period, with 29.5% of mothers delivering preterm, putting the life of the child at a higher likelihood of needing additional medical support [31]. Other studies on maternal amphetamine addiction have found a combination of problems, for example; congenital defects, cardiovascular abnormalities, musculoskeletal abnormalities, cognitive problems, oppositional defiant disorder and attention deficit hyperactivity disorder [22].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of endogenous problems of children, whose mothers are addicted to illicit illegal drugs such as heroin and amphetamines -it has been found that children have significant physical and cognitive problems [22,[30][31][32]. In one study, children around the age of five, of heroin-addicted mothers, were found to have scored significantly lower on verbal, motor, memory and general cognition compared to the general population [4].…”
Section: Introductionmentioning
confidence: 99%